Anti-bribery management systems - requirements with guidance for use (BSI Standards Limited, 2025)
Guidelines that focus on organizational policies preventing bribary. Intended for professional public.
Keywords: Fraud; Social Control Policies; sociologie; Organization and Administration; řízení společenských procesů; podvod; organizace a řízení